INNOVATIVE BUSINESS DEVELOPMENT STRATEGIES IN THE CONDITIONS OF THE POST-WAR ECONOMIC RECOVERY OF UKRAINE - Ганущак, Руслан М.; Маргасова, Вікторія Г. (Journal of Strategic Economic Research, 2024)
The article presents the results of research on the innovative strategy of business development in the conditions of post-war economic recovery. The key strategic imperatives of business development in the conditions of the war and post-war economic recovery of Ukraine were formed, which are based on the Association Agreement with the EU and create new opportunities both on the domestic and international markets. It was established that only about 5.9% of business structures are engaged in the export of goods and services, however, most of the business structures are involved in the production chains of large exporters, which in this way receive certain benefits from trade liberalization. The need to bring the Ukrainian regulatory and legislative framework on competition and institutional structure into compliance with European standards and practices, which in turn should contribute to reducing the monopolization of the economy, and accordingly, motivate the development of the business sector, is substantiated. In the substantiated strategic and innovative perspectives of business development in the conditions of war and post-war recovery of the economy of Ukraine, it is proved that the border regions of Ukraine, which are included in the cross-border partnership program, have additional opportunities to achieve strategic development goals within the framework of the implementation of regional innovative strategies of business development in the conditions of war and post-war recovery of Ukraine’s economy through the use of invested investment resources.